Corporate Governance sebagai Determinan Integritas Laporan Keuangan: Studi Empiris pada Sektor Transportasi dan Logistik Indonesia Periode 2020-2024 - Aniqotunnafiah; Endang Dwi Wahyuningsih; Kasidi; Made Kony Koswara (Jurnal Bingkai Ekonomi (JBE), 2025)
Abstract. This study to examine corporate governance as a determining factor for the integrity of financial reports in the Indonesian transportation and logistics industry. This research investigates the impact of three main components of corporate governance, including managerial ownership, independent board of commissioners, and audit committees on the integrity of financial reports. The research information is sourced from all business entities in transportation and logistics listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024, with a total population of 37 entities and a sample that meets the criteria of 32 entities. The analysis uses multiple linear regression to examine the correlation between independent variables and dependent variables. The findings of this research show that managerial ownership does not have a significant impact on the credibility of financial reports, the independent board of commissioners has a negative and significant effect on the credibility of financial reports, the audit committee has a positive and significant impact on the credibility of financial reports. This result validates that corporate governance components have varying functions in determining the quality of financial reporting in Indonesia's transportation and logistics sector, with the audit committee being the most optimal component in strengthening the credibility of financial reports. Keywords: Corporate governance, Integrity of financial reports, Transportation and logistics